Mathematical Model of Hearing Loss caused by Noise Hazard - Karmand Khdr Ahmad; Grace O. Agaba; Rahman, Bootan (Zanco Journal of Pure and Applied Sciences, 2025)
Hearing loss is a growing public health concern with serious implications for individual’s quality of life. One major cause of hearing loss is exposure to loud noise. This study proposes a mathematical model of hearing loss caused by noise exposure using ordinary differential equations with the aim of providing a framework for understanding the dynamics of the impact of noise hazard. The model is analyzed using local and global stability to determine conditions under which the level of noise pollution remains constant or changes over time and the threshold level beyond which the effect of noise becomes uncontrollable. Sensitivity analysis is performed to determine parameters with greater influence and the ones to control in order to reduce impact of noise exposure. The findings highlight the importance of various parameters in the dynamics of hearing loss by noise exposure and in developing effective strategies for preventing and managing hearing loss.